Methodology for relating the cost of employee turnover, employee retention, and lost production costs - Miguel Salas-Hidalgo, Luis (2024)
Employee turnover generates hidden costs that cannot be recovered, competing with retention costs and their production impact. Using a mathematical algorithm, this study aims to develop a methodology to figure out lost production and related fixed manufacturing overhead costs. This will allow us to estimate the cost of lost output from an employee's layoff until a replacement reaches the required efficiency, considering not only severance costs but also lost production costs. Additionally, we will analyze the cost-benefit of offering salary increases or other incentives against retaining employees, comparing them to the associated costs of increased production and marginal income from the retained employee.